Molecular Characterization of Fructose-1,6-bisphosphate Aldolase From Trichinella spiralis and Its Potential in Inducing Immune Protection - Yang, Yong; Bai, Xue; Li, Chengyao; Tong, Mingwei; Zhang, Peihao; Cai, Wei; Liu, Xiaolei; Liu, Mingyuan (Frontiers in Cellular and Infection Microbiology, 2019)
Trichinella spiralis is a major food-borne parasite worldwide. Trichinellosis caused by T. spiralis is not only a public health problem, but also an economic hazard in food safety. The development of effective vaccines to prevent Trichinella infection in domestic animals and humans is urgently needed for controlling of this zoonosis. Fructose-1, 6-bisphosphate aldolase (FBPA) is involved in energy production in glycolysis and is also associated with many non-glycolysis functions in the parasite, such as adhesion to host cells, plasminogen binding and invasion. FBPA has been considered as a potential vaccine candidate or as a target for chemotherapeutic treatment. Here, we report for the first time the characterization of FBPA of T. spiralis and an evaluation of its potential as a vaccine candidate antigen against T. spiralis infection in mice. The results of qPCR and western blot analysis showed that the Ts-FBPA gene was expressed at various developmental stages of T. spiralis and was also detected in excretory–secretory products (ES) of T. spiralis muscle larvae（ML）. Immunostaining with anti-Ts-FBPA mouse sera indicated that it localized principally to the surface and embryos of this parasitic nematode. Vaccination of mice with recombinant Ts-FBPA (rTs-FBPA) resulted in a Th1/Th2 mixed humoral and cellular immune response with Th2 predominant, as well as remarkably elevated IgE levels. Moreover, mice vaccinated with rTs-FBPA displayed a 48.7% reduction in adult worm burden and 52.5% reduction in muscle larval burden. These studies suggested that Ts-FBPA is promising target for developing effective a vaccine to prevent and control Trichinella infection.